MECHANICAL PROPERTIES PREDICTION OF IG-110 GRAPHITE BY NON DESTRUCTIVE INSPECTION USING ULTRASONIC METHOD - Roziq Himawan; M. Haryanto; M. Budi Setiawan (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2019)
The core structure of high temperature gas cooled reactor is the most important part of the reactor which its integrity must be ensured during operation stage. The structure of reactor core must ensure the position of fuel to be kept in its position, to ensure the control rods can get into the guiding canal, and to ensure the flow of the gas coolant. One of the stressor of the graphite material degradation is neutron exposure. The impact of neutron exposure is the change in mechanical properties such as modulus of elasticity. In order to ensure the integrity of the materials, an in-service non-destructive inspection is implemented. The aim of this study is to develop non-destructive inspection method in order to predict mechanical properties of graphite materials. Inspections were done using Ultrasonic Flaw Detector with 35×35×55 [mm] block-shaped specimens made of graphite IG-110. Two types of transducer were used to generate longitudinal and transversal waves with the same frequency of 5 MHz. Two mechanical properties were predicted, that are isotropic characteristic and the modulus of elasticity. The predicted value of the modulus of elasticity was verified by conducting compressive tests using 10×10×10 [mm] cube specimens. According to the ultrasonic propagation velocities resulted from ultrasonic inspection results showed that the graphite IG-110 is an isotropic material. From the calculation of the modulus of elasticity based on measurement results of transversal and longitudinal waves propagation, IG-110 graphite has a value of modulus of elasticity of 9.1 GPa. Compared to the modulus of elasticity measured from compressive test, this value was 10% lower. It can be concluded that the ultrasonic non-destructive inspection can be used to predict mechanical properties of the IG-110 graphite.